Milenascopia gen. nov. (Orthoptera: Proscopiidae) from the Brazilian Amazon Basin and a pictorial key to Proscopiini genera - Queiroz, Larissa Lima De; Rafael, José Albertino (Zootaxa, 2019)
A new genus of Proscopiidae, Milenascopia gen. nov., is described from Brazil, with two included species, namely Milenascopia bilineata gen. nov., sp. nov. (type-species) and Milenascopia tenuis gen. nov., sp. nov. A pictorial key of Proscopiini, based on the male genitalia is provided.